2012
DOI: 10.1136/annrheumdis-2012-202469
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statement on blocking the effects of interleukin-6 and in particular by interleukin-6 receptor inhibition in rheumatoid arthritis and other inflammatory conditions

Abstract: BackgroundSince approval of tocilizumab (TCZ) for treatment of rheumatoid arthritis (RA) and juvenile idiopathic arthritis (JIA), interleukin 6 (IL-6) pathway inhibition was evaluated in trials of TCZ and other agents targeting the IL-6 receptor and ligand in various RA populations and other inflammatory diseases. This consensus document informs on interference with the IL-6 pathway based on evidence and expert opinion.MethodsPreparation of this document involved international experts in RA treatment and RA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 104 publications
(111 reference statements)
2
81
0
4
Order By: Relevance
“…Anaphylactic reaction was more common in the toclizumab 4mg/kg group than the 8mg/kg group [28]. Antibodies to tocilizumab occurred in about 2-4% of the patients although this did not seem to predispose the hypersensitivity reactions [28].…”
Section: Other Safety Profilementioning
confidence: 89%
See 3 more Smart Citations
“…Anaphylactic reaction was more common in the toclizumab 4mg/kg group than the 8mg/kg group [28]. Antibodies to tocilizumab occurred in about 2-4% of the patients although this did not seem to predispose the hypersensitivity reactions [28].…”
Section: Other Safety Profilementioning
confidence: 89%
“…A recent Consensus indicated that tocilizumab may be used in adult patients with active RA, normally with at least moderate disease activity according to a validated composite measure, who have had an inadequate response to, or intolerance of at least one synthetic DMARD and/or a TNF-inhibitor [28]. In 2012, both the National Institute for Health and Clinical Excellence (NICE) of the United Kingdom and the Food and Drug Administration (FDA) agency of the United States have expanded the approved indication of tocilizumab to be used as a "first-line biological agent" in RA patients who have had an inadequate response to one or more synthetic DMARDs.…”
Section: Tocilizumab and Other Il-6 Agents Currently Under Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…TCZ, either as monotherapy or in combination with MTX, was significantly more efficacious than MTX alone [32] and it is possibly superior to adalimumab in monotherapy. The FDArecommended dose is 4 mg/kg administered via the IV route every 4 weeks, and 162 mg administered via the subcutaneous route every other week, followed by an increase to 8 mg/kg (i.v., q4w) or 162 mg (s.c., qw) based on clinical response [33] and [34]. SC formulations of biologic DMARD have been developed in order to facilitate their use outside hospitals by permitting self-administration.…”
Section: Abataceptmentioning
confidence: 99%